2017
DOI: 10.3346/jkms.2017.32.5.782
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Urinary Angiotensinogen Associated with Deterioration of Kidney Function in Patients with Type 2 Diabetes Mellitus

Abstract: Urinary angiotensinogen (AGT) is potentially a specific biomarker for the status of the intrarenal renin-angiotensin system (RAS) in patients with diabetes mellitus. We explored whether changes in urinary AGT excretion levels were associated with the deterioration of kidney function in type 2 diabetes patients with preserved kidney function. Urinary baseline AGT levels were measured in 118 type 2 diabetic patients who were not taking RAS blockers and who had estimated glomerular filtration rates (eGFRs) ≥ 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The first experimental studies of RAS in DM used alloxan-DM or STZ-DM rat models (Table 3A). Preclinical evidence for an activated renal RAS in DM is suggested by our and others studies on increased synthesis and urinary secretion of renal angiotensinogen (Zimpelmann et al, 2000;Saito et al, 2009;de Alencar Franco Costa et al, 2015;Lee et al, 2017) (Figure 2 shows urinary angiotensinogen as a potential biomarker). STZ-induced DM in rats caused a 69% increase of Ang II in the renal interstitial fluid, which was decreased 27% by aliskiren (6 weeks' treatment) (Matavelli et al, 2012).…”
Section: Discussionmentioning
confidence: 61%
“…The first experimental studies of RAS in DM used alloxan-DM or STZ-DM rat models (Table 3A). Preclinical evidence for an activated renal RAS in DM is suggested by our and others studies on increased synthesis and urinary secretion of renal angiotensinogen (Zimpelmann et al, 2000;Saito et al, 2009;de Alencar Franco Costa et al, 2015;Lee et al, 2017) (Figure 2 shows urinary angiotensinogen as a potential biomarker). STZ-induced DM in rats caused a 69% increase of Ang II in the renal interstitial fluid, which was decreased 27% by aliskiren (6 weeks' treatment) (Matavelli et al, 2012).…”
Section: Discussionmentioning
confidence: 61%
“…Urinary AGT and renin excretion are negatively correlated with eGFR [21,27,29], but the relationship between urinary AGT or renin excretion and changes in renal function has not been well studied. Previous studies have suggested that baseline AGT excretion may have limited value as a prognostic factor in predicting changes in renal function during RAS-inhibitor treatment, although it has a negative correlation with changes in renal function without RAS inhibitors [8,27,30,31]. RAS inhibitors seem to attenuate the differences in renal function changes between patients with high and low urinary AGT by inhibiting intrarenal RAS and subsequently decreasing proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…But in recent years, with the deeper and wider research on the RAS, AGT, a principal substrate of AngII, has been recognised as a predictor for some important diseases and positively correlated with disease severity. For example, urinary AGT is an early predictor for acute cardiorenal syndrome and acute decompensated heart failure (Lee et al, ). And urinary AGT might be useful as an early biomarker of activation of the renin–angiotensin system in diabetic nephropathy (Satirapoj, Siritaweesuk, & Supasyndh, ).…”
Section: Discussionmentioning
confidence: 99%